Diseminasi Etika Bisnis & Content Creator kepada Karang Taruna di Kelurahan Sukorame - Hakiki, Soniya Auliya Sabilah; Prabowo, Budi; Hidayat N, Rusdi; Dwiridhotjahjono, Jojok (Jurnal Bisnis Indonesia, 2024)
Dissemination is an act of dissemination aimed at the younger generation with the aim of gettingmore data, raising awareness, tolerance and use of the data. Almost every region in Indonesia hasyouth organizations which are usually called youth organizations. Karang Taruna can be a forum thatexists for the improvement of the young generation, non-partisan, which is built on the basis ofawareness and a sense of social responsibility towards young individuals and society, especially theyoung generation in village/sub-district areas and social communities that reach a break-even pointwith this in essentially locked in the field of social welfare. Even more so in the business world. Thereis a moral code that must be followed for effective trading which is often called business ethics.Meanwhile, a content creator is a third party who relevantly shapes the reviews and purchasingdecisions of other customers. Apart from that, the research method used is descriptive qualitative.Data collection techniques are carried out through observation, socialization, interviews anddocumentation. The data analysis technique in this research was carried out through a process of datareduction, data collection, data presentation, and drawing conclusions.Keywords: Dissemination; Karang Taruna; Business Ethics; and Content Creator